2008
DOI: 10.1186/1743-422x-5-107
|View full text |Cite
|
Sign up to set email alerts
|

Iota-Carrageenan is a potent inhibitor of rhinovirus infection

Abstract: Background: Human rhinoviruses (HRVs) are the predominant cause of common cold. In addition, HRVs are implicated in the worsening of COPD and asthma, as well as the loss of lung transplants. Despite significant efforts, no anti-viral agent is approved for the prevention or treatment of HRV-infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(200 citation statements)
references
References 34 publications
(40 reference statements)
6
193
0
1
Order By: Relevance
“…Compounds 1 and 3 – 10 were tested for antivirus effects on H1N1 by the CPE inhibition assay [21,22], separately. The IC 50 values of 1 , 3 – 10 and ribavirin (positive control) were 75.5 ± 2.2, 41.5 ± 4.5, 62.6 ± 3.9, 106.5 ± 4.2, 28.9 ± 2.2, 6.8 ± 1.5, 94.5 ± 3.0, 113.8 ± 4.9, 156.6 ± 4.0, and 38.8 ± 1.5 μM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 1 and 3 – 10 were tested for antivirus effects on H1N1 by the CPE inhibition assay [21,22], separately. The IC 50 values of 1 , 3 – 10 and ribavirin (positive control) were 75.5 ± 2.2, 41.5 ± 4.5, 62.6 ± 3.9, 106.5 ± 4.2, 28.9 ± 2.2, 6.8 ± 1.5, 94.5 ± 3.0, 113.8 ± 4.9, 156.6 ± 4.0, and 38.8 ± 1.5 μM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antiviral activity against H1N1 was evaluated by the CPE inhibition assay [21,22]. Confluent MDCK cell monolayers were firstly incubated with influenza virus (A/Puerto Rico/8/34 (H1N1), PR/8) at 37 °C for 1 h. After removing the virus dilution, cells were maintained in infecting media (RPMI 1640, 4 μg/mL of trypsin) containing different concentrations of test compounds at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Carrageenan acts primarily by preventing the binding or the entry of virions into cells (Buck et al 2006, Grassauer et al 2008). This finding is consistent with the fact that carrageenan resembles heparan sulfate, an HPV cell-attachment factor.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The main three types of carrageenans are λ-, κ-, and ι-carrageenan, and each show different inhibitory effects on different viruses [32,33,34,35,36,37]. Buck et al demonstrated that carrageenans could inhibit the initial infection process of human papillomavirus (HPV), and the antiviral effect of ι-carrageenan is better than that of λ- and κ-carrageenans [38].…”
Section: The Antiviral Effects and Structure–activity Relationshipmentioning
confidence: 99%